Revelations of short films: approximation with Brazilian guiding document for comprehensive adolescente health care. (Revista Brasileira Multidisciplinar, 2023)
The present study aims to present guidelines and social diagnoses reported by adolescents and discuss their interface with the National Guidelines for Comprehensive Health Care for Adolescents and Young People in Health Promotion, Protection and Recovery. This is a documentary, theoretical and reflective study, carried out from the analysis of 39 short films available on the website of a project entitled “É Nóis na Fita” and later related to the guiding document for health care for adolescents in Brazil. Brazil. During the analysis, four thematic categories emerged: “Family relationships and influences on adolescence”; “Minorities and Inequities”; “Social relations, identities and projects”; and “Factors that make youth vulnerable”. Thus, it was concluded that there is consonance between the guidelines and the structuring axes of the guiding document, except for issues related to family relationships, with indications of expanding its consideration. Soon, the shorts were powerful for youthful voice and revelations.
Keywords: adolescent; comprehensive health care; adolescent health; social vulnerability; minority health